Women and Devotional Literature in the Middle Ages Giving Voice to Silence. Essays in Honour of Catherine Innes-Parker. - Gunn, Cate (Gender in the Middle Ages Series., 2023)
Essays on women and devotional literature in the Middle Ages in commemoration and celebration of the respected feminist scholar Catherine Innes-Parker.